Blood pressure, flow, and peripheral resistance of digital arteries in vibration syndrome. - Futatsuka, M (1983)
The peripheral circulation was studied in 19 lumberjacks and in 12 control subjects. Twelve of the lumberjacks were free from vascular symptoms and seven had vibration induced white finger (VWF). Using the strain-gauge plethysmographic technique, the digital circulation was examined at rest, during cooling of the upper body, and during heating of the upper body. At rest and during vasodilatation no significant differences were found between the lumberjacks and the controls. During reflexive vasoconstriction, digital blood flow in the upper body was more reduced in lumberjacks with VWF than in control subjects. Furthermore, digital blood pressure of the lumberjacks with VWF fell more than in the control group. The peripheral resistance also increased more, but this difference was not statistically significant. There was no evidence that the exaggerated vasoconstriction of VWF resulted from a narrowing of the lumen of arterioles due to hypertrophy of the vessel wall. The present findings suggest that VWF is produced by the highly sensitive responsiveness of the affected vessel to normal vasoconstrictor stimuli.